P3.288 Antimicrobial Susceptibility and Molecular Epidemiologic Clusters of Neisseria Gonorrhoeae Strains in 2007 and 2012 in Nanjing, China. (13th July 2013) - Chen, S; Yin, Y; Chen, X; Dai, X; Yu, R; Han, Y; Unemo, M
Abstract : Background: Gonorrhoea is the most prevalent bacterial sexually transmitted infection globally. It is of grave concern that Neisseria gonorrhoeae has developed resistance to mainly all antimicrobials introduced for treatment. China is located in the WHO Western Pacific Region (WPR), where most gonococcal antimicrobial resistance (AMR) has originated. However, the information regarding AMR and particularly molecular epidemiology of N. gonorrhoeae strains in China is highly limited. This study investigated the AMR and molecular epidemiologic clusters of N. gonorrhoeae in 2007 and 2012 in Nanjing, China. Methods: A total of 204 and 82 N. gonorrhoeae isolates were collected in 2007 and 2012, respectively, in Nanjing, China. The susceptibility to ceftriaxone, spectinomycin, ciprofloxacin and tetracycline were tested using agar dilution method, according to the recommendations from CLSI. NG-MAST was performed for molecular epidemiology and full-length porB sequences were used for phylogenetic analysis. Results: All (100%) isolates were resistant to ciprofloxacin, tetracycline, and 41.6% produced β-lactamase. According to the CLSI breakpoints, all (100%) isolates were susceptible to spectinomycin (S < = 32 µg/ml) and 99.7% to ceftriaxone (S≤ 0.25 µg/ml). However, using the European breakpoints 5.2% of the isolates were resistant to ceftriaxone (EUCAST, S≤ 0.125 µg/ml). The most prevalent NG-MAST clusters in 2007 included ST568 (n = 13), ST270 (n = 9), ST421 (n = 7), and ST2288 (n = 5). The most prevalent clusters in 2012 included ST1053 (n = 4), ST2318 (n = 4), ST5990 (n = 4), and ST1614 (n = 4). Isolates with identical or phylogenetically similar STs had similar MICs of ceftriaxone. Many novel STs were identified. Conclusion: Ceftriaxone and spectinomycin can continuously be recommended for treatment of gonorrhoea in Nanjing, China. The different molecular epidemiologic clusters in 2007 and 2012 indicate fluctuations in the sexual networks in Nanjing. The identified correlations between NG-MAST STs and MICs of antimicrobials suggest that NG-MAST can supplement the AMR surveillance in China, which needs to be further strengthened.